Pharmacotherapy in body dysmorphic disorder: relapse prevention and novel treatments. (3rd July 2019) - Dong, Nancy; Nezgovorova, Vera; Hong, Kevin; Hollander, Eric
ABSTRACT: Introduction : Body dysmorphic disorder is a debilitating disorder that often presents with significant delusionality, low insight, and both medical and psychiatric comorbidities, presenting a challenge for treatment and long-term management. Its typically chronic course requires that therapy be continued indefinitely, but only a few studies of long-term pharmacotherapeutic management exist. Areas covered : The authors discuss the current understanding of body dysmorphic disorder, focusing specifically on: epidemiology, clinical presentation, challenges in treatment, treatment options, and the importance of the further study of the long-term management of the disorder. Expert opinion : Serotonin reuptake inhibitors are the established drug of choice in patients with body dysmorphic disorder. Initial studies suggest that other agents such as augmentation antipsychotic medication may also be of use in combination with serotonin reuptake inhibitors, but there is a lack of studies comparing new treatments to serotonin reuptake inhibitors. Due to the chronic nature of body dysmorphic disorder, further research is needed to clarify the role of pharmacotherapy in long-term management and relapse prevention. Future studies should explore the long-term use of therapies and combinations of different therapeutics with the goal of effectively managing this debilitating, chronic condition.